Go red for women - Kornacewicz-Jach, Zdzisława; Kossuth, Irmina; Czechowska, Małgorzata (Menopause Review/Przegląd Menopauzalny, 2006)
Cardiovascular disease (CVD) is the most common cause of death in both men and women. Clinical and epidemiologic studies have shown differences among women and men with CVD in disease processes, clinical presentations and outcomes. There is a reasonable necessity to enhance the enrollment of women in cardiovascular clinical trials that it could be proportional to the prevalence of cardiovascular disease among women in the general population.